Hybrid methods for a finite family of G-nonexpansive mappings in Hilbert spaces endowed with graphs - Raweerote Suparatulatorn (2018)
© 2017 Kalasalingam University In this paper, we prove a strong convergence theorem for two different hybrid methods by using CQ method for a finite family of G-nonexpansive mappings in a Hilbert space. We give an example and numerical results for supporting our main results and compare the rate of convergence of the two iterative methods.